2021
DOI: 10.1128/jvi.01638-20
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of gQ1 and gQ2 in Human Herpesvirus 6A and 6B Regulates the Viral Tetramer Function for Their Receptor Recognition

Abstract: Human herpesvirus 6A (HHV-6A) and HHV-6B use different cellular receptors, human CD46 and CD134, respectively and have different cell tropisms although they have 90% similarity at the nucleotide level. An important feature that characterizes HHV-6A/6B is the glycoprotein H (gH)/gL/gQ1/gQ2 complex (a tetramer) that each virus has specifically on its envelope. Here, to determine which molecules in the tetramer contribute to the specificity for each receptor, we developed a cell-cell fusion assay system for HHV-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…At 24 h posttransfection, firefly and Renilla luciferase activities were independently assayed using the dual-luciferase reporter assay system (Promega). The luciferase activity (Fluc/Rluc) was calculated as follows: (firefly luciferase activity)/(Renilla luciferase activity) (59,63,64). To analyze the effect of inhibitors, transfected cells were untreated or treated with 10 ng of TNF-a or 10 mM colforsin as an inducer of NF-k B and CRE, respectively, at 24 h after transfection.…”
Section: Methodsmentioning
confidence: 99%
“…At 24 h posttransfection, firefly and Renilla luciferase activities were independently assayed using the dual-luciferase reporter assay system (Promega). The luciferase activity (Fluc/Rluc) was calculated as follows: (firefly luciferase activity)/(Renilla luciferase activity) (59,63,64). To analyze the effect of inhibitors, transfected cells were untreated or treated with 10 ng of TNF-a or 10 mM colforsin as an inducer of NF-k B and CRE, respectively, at 24 h after transfection.…”
Section: Methodsmentioning
confidence: 99%
“…Upon testing this hypothesis using both immunofluorescence ( Figure 10 ) and RT-qPCR ( Figure 11 ), results showed that GAD67-positive cells are not only expressing CD134 and CD46, but CD134 expression was higher under all conditions (i.e., uninfected, HHV-6A infected, HHV-6B infected). Although the relative binding affinity of HHV-6A versus HHV-6B on each of these cell surface receptors is somewhat unclear ( 36 ; 37 ), it is known that HHV-6B can use CD46 but preferentially binds to CD134. Thus, it is reasonable to suggest that HHV-6B has an advantage over HHV-6A in terms of receptor availability, attachment, and entry into susceptible hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in biological characteristics, pathogenicity and genetic sequences of HHV‐6 led to identifying two variants called HHV‐6A and HHV‐6B. The similarity of these Variants' sequences is 90% 6,7 . HHV‐6A, HHV‐6B, and HHV‐7 create the Roseolovirus genus 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The similarity of these Variants' sequences is 90% 6,7 . HHV‐6A, HHV‐6B, and HHV‐7 create the Roseolovirus genus 7 . HHV‐6 infection is widespread in the human population, and roseola usually occurs in the first year of infancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation